Literasi Sociopreneurship dan Sustainable Lifestyle Peserta Didik SMP Negeri 25 Semarang di Tengah Covid-19 - Ramadhania, Melati; Mulianingsih, Ferani (Sosiolium: Jurnal Pembelajaran IPS, 2021)
SMP Negeri 25 Semarang develops an environment-based curriculum in order to develop a school culture that cares about the environment while teaching children to be entrepreneurship. The purpose of this study was to find out (1) to determine the level of sociopreneurship in students in the midst of the COVID-19 pandemic (2) the Sustainable Lifestyle attitude possessed by students in the midst of the COVID-19 pandemic. This research method is qualitative with data collection techniques of observation, interviews, documentation, and perposive sampling. The research location is at SMP Negeri 25 Semarang. The data validity technique uses source triangulation. The results of this study indicate that (1) the level of sociopreneurship literacy of students in grades VII, VIII, IX of SMP Negeri 25 Semarang in the midst of the COVID-19 pandemic shows a sufficient category (2) the level of sustainable life style of students of SMP Negeri 25 Semarang in the midst of the COVID-19 pandemic indicates high category.